(untitled) (Journal of Student Affairs in Africa, 2021)
In March 2020, the South African President Mr Cyril Ramaphosa announced a national lockdown due to the rising cases of the Covid‑19 pandemic. As a result, some of the higher education institutions closed under lockdown level 5 and strategies had to be developed to adapt to the “new norm”. Consequently, students and the living and learning spaces in South Africa were affected, necessitating therefore that transformation in all spheres takes place. This study, through a qualitative research design, investigated the effect of Covid‑19 on students and the living and learning spaces at a selected university in South Africa. Fifteen students and ten Residence Advisors (RAs) were telephonically interviewed. The results revealed that the living and learning spaces had been significantly transformed by the Covid‑19 pandemic. The operations of these spaces had been compelled to change in order to comply with the Covid‑19 regulations, such that student learning was shifted from face-to-face to online learning. This meant more time spent indoors, stricter measures now in place and the RA roles having been broadened to ensure that they also monitor compliance. The study also noted that even after the pandemic, things will still take time to get back to normal. This article concludes that Covid‑19 has had a huge effect on the living and learning spaces as well as students at the selected university and that both students and staff should play their roles effectively to ensure that everyone remains safe.